Survey of living conditions in the arctic : results - Poppel, Birger; Kruse, Jack; Duhaime, Gérard; Abryutina, Larissa (Anchorage : Institute of Social and Economic Research, University of Alaska Anchorage, 2024)
Major findings of the Survey of Living Conditions in the Arctic (SLiCA) are: (1) A combination of traditional activities and cash employment is the prevailing lifestyle of Arctic indigenous peoples; (2) family ties, social support of each other, and traditional activities have a lot to do with why indigenous people choose to remain in Arctic communities; (3) well-being is closely related to job opportunities, locally available fish and game, and a sense of local control. Well-being and depression (and related problems like suicide) are flip sides of the same coin. Improving wellbeing may reduce social problems; and, (4) health conditions vary widely in the Arctic: three-in-four Greenlandic Inuit self-rate their health as at least "very good" compared with one-in-two Canadian and Alaska Inuit and one-in-five Chukotka indigenous people. Findings are based on 7,200 interviews in a probability sample of Iñupiat settlement regions of Alaska, the four Inuit settlement regions of Canada, all of Greenland, and the Anadyrskij, Anadyr, Shmidtovs, Beringovskij, Chukotskij, Iujl'tinskij, Bilibinskij, Chaunskij, Providenskij, Uel'Kal' districts of Chukotka. Indigenous people and researchers from Greenland, Russia, Canada, the United States, Denmark, Norway, Sweden, and Finland collaborated on all phases of the study.